Performance Analysis of Voltage Stability Against Sudden Load Changes in Voltage Controlled Inverters for Distributed Generation - Arvind H. Kadam; Keerthi Unni; Sushil Thale (International Journal of Applied Power Engineering (IJAPE), 2014)
Distributed Generation (DG) is playing an important role in the field of electricity generation by being a viable alternative to the Centralized Power Generation (CPG). Although, distributed generation has many advantages, it has some issues in the fields of protection, power control, stability, islanding detection etc. Amongst all the issues, this paper attempts to highlight the issue of voltage stability under sudden changes in loading conditions in a distributed generation systems operating in stand-alone mode. Proper design and tuning of compensators for closed loop operation in DG systems can ensure voltage stability. As the load demand increases, the output voltage of DG usually dips for a short time owing to the weak (smaller capacity) nature of renewable sources, after which it returns to steady state. This fall in the voltage profile could prove to be harmful if the settling time is more. The simulation and hardware results illustrate that, accurate compensator design, is one of the key factor in maintaining the voltage stability in DG system. This paper explores the effect of proper compensator design in maintaining voltage stability of DG.